RELASI AKTOR DALAM IMPLEMENTASI KEBIJAKAN PENDIDIKAN MENENGAH DI KOTA MATARAM - Muhammad Ali (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2020)
Abstract, Secondary education policy needs to be improved by a process which is a strategic alternative to improve the quality of education. This paper examines the relation of actors in the implementation of secondary education policy in the city of Mataram which focuses on senior secondary education as an education sub-system by formulating and implementing education-related policies that are trademarks for the achievement of policy objectives. The Key to Policy Implementation uses a participatory approach in public policy making in education supported by 4 (four) factors as a driver of successful policy implementation. But in reality there are causes of the implementation of policies that have not optimally reached their objectives, namely: a). Communication b). Resources (Resources), c). Implementor Attitudes (Dispositions), and d). Bureaucratic Structure (Bureaucratic Structure). Then, on the other hand, the Government's relation with actors outside the government is not yet optimal, where the government has not effectively built relationships with the community and the business world so that governance has not been created in the implementation of secondary education policies. This condition requires improvement of aspects of policy implementation and improvement of coordination between actors and organizational culture towards the achievement of secondary education policy objectives in supporting governance in the city of Mataram. Keywords: Policy Implementation, Secondary Education, Governance Abstrak, Kebijakan pendidikan menengah perlu ditingkatkan dengan suatu proses yang merupakan alternatif strategis untuk meningkatkan kualitas pendidikan. Tulisan ini mengkaji relasi aktor dalam implementasi kebijakan pendidikan menengah di kota mataram yang menitikberatkan pada pendidikan menengah atas sebagai sub sistem pendidikan dengan merumuskan dan melaksanakan kebijakan terkait pendidikan yang menjadi trademark unttuk tercapainya tujuan kebijakan. Kunci Implementasi kebijakan menggunakan pendekatan partisipatory dalam pengambilan kebijakan publik bidang pendidikan yang ditopang oleh 4 (empat) faktor sebagai pendorong keberhasilan implementasi kebijakan. Namun secara realitas adanya penyebab implementasi kebijakan yang belum secara optimal mencapai tujuannya yaitu: a). Komunikasi b). Sumber Daya (Resources), c). Sikap Implementor (Dispositions), dan d). Struktur Birokrasi (Bureaucratic Structure). Kemudian pada sisi yang lain relasai Pemerintah dengan aktor di luar pemerintah yang belum optimal, dimana pemerintah belum secara efektif membangun relasi dengan masyarakat dan dunia usaha sehingga belum tercipta governance dalam implementasi kebijakan pendidikan menengah. Kondisi ini memerlukan pembenahan terhadap aspek-aspek implementasi kebijakan dan peningkatan koordinasi antar aktor dan budaya organisasi ke arah pencapaian tujuan kebijakan pendidikan menengah dalam mendukung governance di kota Mataram. Kata Kunci: Implementasi Kebijakan, Pendidikan Menengah, Governance